Circulation of Venusian Atmosphere at 90–110 km Based on Apparent Motions of the O2 1.27 μm Nightglow From VIRTIS‐M (Venus Express) Data. Issue 5 (15th March 2018) - Gorinov, D. A.; Khatuntsev, I. V.; Zasova, L. V.; Turin, A. V.; Piccioni, G.
Abstract: The paper is devoted to the investigation of Venus mesosphere circulation at 90–110 km altitudes, where tracking of the O2 (a 1 Δg ) 1.27 μm nightglow is practically the only method of studying the circulation. The images of the nightglow were obtained by VIRTIS‐M on Venus Express over the course of more than 2 years. The resulting global mean velocity vector field covers the nightside between latitudes 75°S–20°N and local time 19–5 h. The main observed mode of circulation is two opposite flows from terminators to midnight; however, the wind speed in the eastward direction from the morning side exceeds the westward (evening) by 20–30 m/s, and the streams "meet" at 22.5 ± 0.5 h. The influence of underlying topography was suggested in some cases: Above mountain regions, flows behave as if they encounter an "obstacle" and "wrap around" highlands. Instances of circular motion were discovered, encompassing areas of 1, 500–4, 000 km. Plain Language Summary: Recent developments in the studies of Venus atmosphere reveal an intriguing phenomenon of stationary gravity waves, which emerge from the surface, interacting with the cloud layer up to ~70 km. In this paper, analysis of the oxygen nightglow on the nightside of Venus using data from VIRTIS instrument (Venus Express spacecraft) delivers clues that the atmosphere at 90–110 km altitude can as well be influenced by such mechanisms. The horizontal motion, obtained from tracking the displacements of the bright features of the nightglow, appears to hold disturbances, the positions of which in some cases coincide with highlands directly below or shifted by several degrees. The nightglow itself, known to manifest an extremely irregular behavior, sometimes repeats the shapes of the mountain ranges below. As another major result, the mean horizontal circulation, calculated for the nightside southern hemisphere, does represent neither superrotation, nor subsolar‐to‐antisolar circulation, nor a superposition of the two. Both the zonal and the meridional components of the motion have different magnitudes and direction before and after midnight. The results of this research further our knowledge on the upper atmosphere of Venus and pose a challenge for the global circulation models. Key Points: The horizontal wind velocity in Venus atmosphere at 90–110 km was obtained from the O2 (a 1 Δg ) nightglow tracking Average zonal component from the morning side exceeds its opposite from the evening side by 20–30 m/s; they "meet" at 22–23 h local time The influence of the underlying topography on the wind direction was suggested in some cases